EFFECTS OF LIBRARY INSTRUCTION ON SATISFACTION WITH THE USE OF LIBRARY AND ITS SERVICES: A STUDY OF UNDERGRADUATE STUDENTS IN FIVE UNIVERSITIES IN THE SOUTHERN PART OF NIGERIA - Esse, Ugwunwa Chinyere (European Scientific Journal, ESJ, 2014)
User education is an academic programme that is designed by higher institutions to educate library users on how to effectively utilize library resources and its services. The saying that a University is a library surrounded by other buildings is a clear pointer to the centrality of library to educational pursuits. User education and use of library remain one huge challenge. It is established that library users all over the world face various challenges which impact the extent to which the resources available are put to maximum and effective use. This paper is an exploration to evaluate the effect of library education programme on Undergraduate Students of Southern Part of Nigeria. It attempts to answer questions like how have Librarians positioned the library for effective use of students? Are library users given adequate and impactful user education? The paper discovered that although user education programmes exist and users are of the opinion that they helped boost their use of library, the library still needs to intensify its efforts to educate library users through setting up of additional methods of user education in order to achieve excellence in educational pursuit.